Endoscopy in the Diagnosis of Small Intestinal Tumors. Issue 3 (1997) - Kawaguchi, M.; Saitou, Y.; Sakai, Y.; Tani, Y.; Midorikawa, S.; Sanji, T.; Handa, Y.; Morita, S.; Ohno, H.; Yosida, H.; Turui, M.; Misaka, R.; et al.
Abstract : The importance of endoscopy in the diagnosis of small intestinal tumors was evaluated in 15 patients with small intestinal tumors treated in our hospital. Two tumors were benign, and 13 were malignant (carcinoma in 5 patients, malignant lymphoma in 5 and leiomyosarcoma in 3). The presence of lesions could be determined by X-rays before surgery, but definitive diagnoses were difficult. When preoperative endoscopy of the small intestine was possible accurate preoperative diagnoses could be made based on the endoscopic findings and biopsies taken under direct vision. Endoscopy is therefore very important for the diagnosis of small intestinal tumors. It is necessary to develop small intestinal endoscopes that are easier to insert.